1987
DOI: 10.1093/nar/15.14.5749
|View full text |Cite
|
Sign up to set email alerts
|

Comparative inhibition of chloramphenicol acetyltransferase gene expression by antisense oligonucleotide analogues having alkyl phosphotriester, methylphosphonate and phosphorothioate linkages

Abstract: Several classes of oligonucleotide antisense compounds of sequence complementary to the start of the mRNA coding sequence for chloramphenicol acetyl transferase (CAT), including methylphosphonate, alkyltriester, and phosphorothioate analogues of DNA, have been compared to "normal" phosphodiester oligonucleotides for their ability to inhibit expression of plasmid-directed CAT gene activity in CV-1 cells. CAT gene expression was inhibited when transfection with plasmid DNA containing the gene for CAT coupled to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(72 citation statements)
references
References 63 publications
3
69
0
Order By: Relevance
“…Substitution of the phosphodiester backbone of native DNA with phosphorothioate moieties markedly augments resistance to nuclease digestion. 35,36 Phosphorothioates, however, have also been found to bind with high affinity to a large number of proteins 37,38 presumably the result of alterations in the presentation of negative charges. Without appropriate controls, sequence-independent effects caused by phosphorothioate chemistry can be mistakenly attributed to a true antisense effect.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of the phosphodiester backbone of native DNA with phosphorothioate moieties markedly augments resistance to nuclease digestion. 35,36 Phosphorothioates, however, have also been found to bind with high affinity to a large number of proteins 37,38 presumably the result of alterations in the presentation of negative charges. Without appropriate controls, sequence-independent effects caused by phosphorothioate chemistry can be mistakenly attributed to a true antisense effect.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal length of a PNA or PMO depends on achieving a balance between specificity and efficacy and is estimated to be about 15 to 25 bases (2, 14, 16, 21, 30). However, experimental evidence suggests that many factors, such as cellular uptake or invasion of mRNA secondary structure, influence efficacy and can tip the balance in favor of shorter antisense oligomers (13,15,19,23,31).Sequence-specific antibacterial drugs are a recent application of antisense technology (11,12,17,24,25,33). Nielsen and coworkers (13) have shown that PNA in the 9-to 12-mer range were more active inhibitors than larger oligomers in Escherichia coli.…”
mentioning
confidence: 99%
“…The optimal length of a PNA or PMO depends on achieving a balance between specificity and efficacy and is estimated to be about 15 to 25 bases (2, 14, 16, 21, 30). However, experimental evidence suggests that many factors, such as cellular uptake or invasion of mRNA secondary structure, influence efficacy and can tip the balance in favor of shorter antisense oligomers (13,15,19,23,31).…”
mentioning
confidence: 99%
“…All oligodeoxyribonucleotides (oligonucleotides) were synthesized on an Applied Biosystems 380B DNA synthesizer. Phosphorothioates containing sulfur at each internucleotide linkage were prepared by sulfurization of the corresponding oligonucleotide hydrogen phosphonates by using Applied Biosystems recommended synthesis cycles and adaptations of previously described methods (36)(37)(38).…”
mentioning
confidence: 99%